Effect of feeding level on growth rate, carcass characteristics and meat quality of thin tailed lambs - N. Luthfi; R. Adiwinarti; A. Purnomoadi; E. Rianto (Diponegoro University, 2022)
A study was conducted to investigate the growth rate and carcass characteristics of lambs under different feeding levels. Twenty one lambs (3 months old) were allocated into 3 treatments of feeding levels, namely 4% of body weight (BW) (T1), 5.5% of BW (T2) and provided ad libitum (T3). The diet contained 13.74% of CP and 61.79% of TDN. The lambs were raised to reach 25 kg BW, before being slaughtered. The parameters observed were dry matter intake (DMI), dry matter digestibility (DMD), body weight gain (BWG), feed conversion ratio (FCR), carcass production, meat-bone ratio (MBR), fat distribution, chemical composition of meat and fatty acids profile. The data obtained were analyzed by analysis of variance and continued by Duncan's multi-range test if there was any significant difference among the treatments. The results showed that the average of DMD was 59.71% (P>0.05). The lambs fed T3 had the highest BWG (203 g/day), the lowest FCR (6.8) and the shortest rearing time (67 days) (P<0.01). The average of carcass percentage was 46.36% and meat production was 6,931 g (P>0.05). The lambs of T3 had the heaviest carcass fat (2,698 g), the lightest carcass bone (1,985 g), the highest MBR (3.6), and the highest PUFA to SFA ratio (0.55). It can be concluded that the higher the feeding level resulted in the higher growth rate, the lower feed conversion ratio, higher meat-bone ratio and higher carcass fat production, lower feed conversion ratio and the shorter rearing time; but did not af-fect the meat quality.